Environmental hazards, rigid institutions, and transformative change: How drought affects the consideration of water and climate impacts in infrastructure management. (November 2019) - Ulibarri, Nicola; Scott, Tyler A.
Highlights: Text mining & interviews were used to study drought's effect on infrastructure siting and review. Extent of drought & consideration of drought impacts on infrastructure were closely correlated. Attention to water & climate impacts on infrastructure increased, but not correlated to drought. Slow-onset hazards may not shift institutional norms as easily as fast-onset hazards. Abstract: Climate change necessitates major changes in infrastructure siting, design, and operations. Successful adaptation of infrastructure management requires overcoming thorny institutional challenges including path dependency and isomorphic pressures that inhibit major shifts in norms and practices. Hazards have been posited as a potential trigger for changing long-standing institutions because they can upend stable system states. However, research on the ability of hazards to shift norms and practices is still nascent and focuses on rapid-onset disasters like floods, hurricanes, or fires. This paper uses the 2012–2016 California drought to assess the potential for slow-onset hazards to lead to institutional change. We assess whether it yielded a shift in institutional norms, namely agency application of existing regulations toward enhanced socio-ecological resilience in the face of climate change. We focus on the environmental impact assessment process under the National Environmental Policy Act and the Federal Energy Regulatory Commission's process for licensing hydropower dams. Using computational text analysis of Environmental Impact Statements and participant observation of infrastructure licensing negotiations, we assess whether, over the years of the drought, agencies placed more emphasis on drought issues or climate resilience in analyzing infrastructure siting and design. In EIS documents, we observe a short-term spike in consideration of drought-related impacts and a longer-term increase in water security, suggesting some shifts in institutional practice; however, consideration of climate impacts decreased over the time period. In FERC licensing, there was no consideration of future climate impacts, despite managers' recognition that this posed a problem for projects' future operations. Although these results do not preclude the ability of slow-onset hazards to shift institutional norms, they suggest that doing so is challenging.